POTENSI BUDIDAYA BUAH NAGA DI KENAGARIAN TANJUNG ALAM, KECAMATAN TANJUNG BARU, KABUPATEN TANAH DATAR. - Abdul Aziz; Deded Chandra (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
ABSTRACT ABSTRACT Abdul Aziz. THE POTENTIAL OF DRAGON FRUIT CULTIVATION IN KENAGARIAN TANJUNG ALAM, TANJUNG NEW DISTRICT, TANAH DATAR REGENCY. Thesis, Padang: Faculty of Social Sciences. Padang State University. 2021. This study aims to determine (1) the description of the potential for dragon fruit cultivation in Jorong XII Koto Kenagarian Tanjung Alam, Tanjung Baru District, Tanah Datar Regency. (2) The results of the efforts of dragon fruit cultivators in Jorong XII Koto Kenagarian Tanjung Alam, Tanjung Baru District, Tanah Datar Regency. The type of research approach in this thesis uses a qualitative research approach. Data collection techniques in this study are by using observations, interviews and documentation. The informants in this study were dragon fruit farmers in Tanjung Alam village, Tanjung Baru district, Tanah Datar district. Potential is the wealth possessed by every individual, group, or country in encouraging progress for himself or the community in his environment. This potential is very much needed in determining policies and carrying out development. The results of this study can be seen that, (1) the potential for dragon fruit cultivation in Jorong XII City is very convincing. Dragon fruit cultivation in Jorong XII Koto, Kenagarian Tanjung Alam, Tanjung Baru District, Tanah Datar Regency has the potential to be cultivated. The land in Jorong XII Koto, Kenagarian Tanjung Alam, Tanjung Baru District, Tanah Datar Regency is fertile, loose and not arid, suitable for planting dragon fruit. And also the results of cultivating dragon fruit is more profitable cultivating previous crops such as cassava, cayenne pepper and durian. (2) The results of dragon fruit cultivation in Jorong XII Koto, Kenagarian Tanjung Alam, Tanjung Baru District, Tanah Datar Regency are very satisfying. Cultivating farmers say the average harvest per / month is 300 kg, 500 kg to 700 kg. With a weight of 1 dragon fruit almost reaches 1 kg, the market price in Kenagarian Tanjung Alam, Tanjung Baru District, Tanah Datar Regency is Rp. 15,000 – Rp. 20,000. Keywords: Potential, Farming Yield and Dragon Fruit